Alternative stabilizer for peanut butter - Logan, Nina Marie N.; Galvez, Flor Crisanta F. (1997.)
Alternative stabilizers were used in the preparation of free-flowing peanut butter to determine the effect on the extent of oil separation in this type of peanut butter. Milk powders (soy and cow's milk), protein concentrates at different concentrations (sodium caseinate and soy protein concentrate at 1, 2 and 5% rates of addition) and lard added at 25, 50 and 100% substitution of the oil in the formulation. The extent of oil separation in the products were measured after three months of storage. Viscosity, pH and color of products were likewise determined. Results indicated that although milk powders and protein concentrates improved the stability of the peanut butter, the improvements were not significant. The addition of lard at 50% and 100% substitution, the oil in the formulation did not have any separation of the oil after three months storage at ambient temperature. The maximum cholesterol content in the samples with added lard was found to be only 0.02%.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanut butter